2016
DOI: 10.9790/1959-0504045667
|View full text |Cite
|
Sign up to set email alerts
|

Application of Watson Caring Theory for Nurses in Pediatric Critical Care Unit

Abstract: Caring is considered as the essence of nursing and is the basic factor that distinguishes between nurses and other health professions. The literature is rich of previous studies that focused on perceptions of nurses toward nurse caring behaviors, but less studywas applied in pediatric nurses in different settings. Aim of the study:evaluate the effect of application of Watson caring theory for nurses in pediatric critical care unit. Method(s): A convenience sample of 70 nurses of Pediatric Critical Care Unit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
6
0
2
Order By: Relevance
“…This is congruence with Elbahnasawy et al (2016) who found that above half of nurses reported that heavy workload act as a barrier against Watson theory application. [33] Which is supported by other study findings which demonstrated that heavy workload by inadequate nurse-to-patient ratio was perceived as the greatest barriers to care provision. [13,30] Furthermore, Salimi and Azimpour (2013) presented job satisfaction as the highest score affecting caring behavior.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is congruence with Elbahnasawy et al (2016) who found that above half of nurses reported that heavy workload act as a barrier against Watson theory application. [33] Which is supported by other study findings which demonstrated that heavy workload by inadequate nurse-to-patient ratio was perceived as the greatest barriers to care provision. [13,30] Furthermore, Salimi and Azimpour (2013) presented job satisfaction as the highest score affecting caring behavior.…”
Section: Discussionsupporting
confidence: 57%
“…Which is in line with other researchers who reported that human needs assistance category as the most important caring behaviors as perceived by nurses. [33,34] Similarly to Pajnkihar et al (2017) results which entitled the carative factor needs as the highest caring behaviors as perceived by nurses. [35] This is contradicting with O'Connell and Landers (2008) who reported that the highest score of nurses caring behaviors was related to humanism/faith/hope/sensitivity domain of caring.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have also confirmed that heavy workload is a significant influential factor in the care behaviours of nurses (Kakemam and Raeissi et al, 2019; Shalaby et al, 2018). In a study in this regard, Elbahnasawy et al (2016) reported that heavy workload was one of the barriers to optimal clinical performance (Elbahnasawy et al, 2016). Other studies have also indicated that due to the inappropriate nurse‐to‐patient ratio, the workload of nurses is the most substantial challenge in the provision of high‐quality nursing services (Attia et al, 2013; Modic et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A sua finalidade principal envolve o cuidado por parte da equipa de enfermagem que auxilia a pessoa a ganhar um grau mais elevado de harmonia entre a mente, corpo e alma, o que pode levar ao autoconhecimento, autorrespeito, autocura e autocuidado (Watson, , 2012. A aplicação desta teoria tem vindo a ser realizada no domicílio (Rodrigues et al, 2016), em ambiente hospitalar (Elbahnasawy, Lawend, & Mohammed, 2016), com crianças (França et al, 2017), pacientes com cancro (França et al, 2017;Mendonça, Pereira, Barreto, & Silva, 2018), com idosos (Maygua, Arévalo, Granizo, Herrera, & Jimbo, 2017), familiares (Santos, Souza, Misko, Silva, & Szylit, 2018) e pacientes em cuidados paliativos (França et al, 2017). Tal facto, demonstra a ampla utilização da teoria e a sua aplicabilidade em diversos contextos de saúde e com populações distintas.…”
Section: Finalidadeunclassified